بناء وتطبيق مقياس الاستجابة الانفعالية للاعبي اندية الدرجة الاولى بكرة القدم فى اقليم كردستان - زبير, ا.م.د أري انور (Sulaimani Journal for Humanities, 2023)
The research aims to: 1- Building and applying the emotional response scale for football players 2-To identify the emotional response scale for football players The researcher used the descriptive survey method as it is the most appropriate approach to the nature of the research problem. The researcher chose the research community, which was represented by (2022-2023) first division league players of Kurdistan Region- Iraq, (222) players were chosen as a sample of the research. The researcher extracted the scientific foundations of the scale, after which the basic experience of the scale was applied, as the emotional response scale with its instructions and paragraphs, which were (30) paragraphs, became ready for application to the research sample, which numbered (100) football players, through direct contact with the players after displaying the results. 1- The emotional response scale for football players of first division league of Kurdistan Region of Iraq. 2- (Three) axes were extracted to measure the emotional response for football players of first division league of Kurdistan Region of Iraq. Based on the results of the statistical analysis, the scale items have reached (30) items distributed on the axes as follows: A- The first axis was called the axis (acceptance or rejection) and it contained (10) paragraphs. B- The second axis was called the (emotional reaction) axis, and it contained (10) paragraphs C - The third axis was called the axis (psychological commitment) and it contained (10) paragraphs.